CRIMINAL LAW POLICY AND NON-PENAL EFFORTS IN ADDRESSING JUVENILE DELINQUENCY IN INDONESIA: A LEGAL-CRIMINOLOGICAL REVIEW - Moch Eko Setiyo Budi Utomo; Nur Melia; Dwi Imroatus Sholikah; Burham Pranawa (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2026)
Juvenile delinquency is a multifaceted phenomenon necessitating a comprehensive approach that integrates legal, psychological, and social perspectives. The legal complications arising from a minor's interaction with the criminal justice system significantly impact their psychological well-being and future prospects; thus, a critical analysis of policy effectiveness is imperative. Employing normative legal research, this study demonstrates that the penal approach frequently engenders detrimental stigmatization. Consequently, a paradigm shift toward non-penal measures and the implementation of a double-track system is required, alongside the optimization of conditional sentencing. Furthermore, the concept of 'Reintegrative Shaming'serves as a viable alternative to rehabilitate minors while upholding their fundamental rights as mandated by child protection legislation.